The Cedar Project: resilience in the face of HIV vulnerability within a cohort study involving young Indigenous people who use drugs in three Canadian cities. (December 2015) - Pearce, Margo; Jongbloed, Kate; Richardson, Chris; Henderson, Earl; Pooyak, Sherri; Oviedo-Joekes, Eugenia; Christian, Wunuxtsin; Schechter, Martin; Spittal, Patricia
Abstract Background Indigenous scholars have long argued that it is critical for researchers to identify factors related to cultural connectedness that may protect against HIV and hepatitis C infection and buffer the effects of historical and lifetime trauma among young Indigenous peoples. To our knowledge, no previous epidemiological studies have explored the effect of historical and lifetime traumas, cultural connectedness, and risk factors on resilience among young, urban Indigenous people who use drugs. Methods This study explored risk and protective factors associated with resilience among participants of the Cedar Project, a cohort study involving young Indigenous peoples who use illicit drugs in three cities in British Columbia, Canada. We utilized the Connor-Davidson Resilience Scale to measure resilience, the Childhood Trauma Questionnaire to measure childhood maltreatment, and the Symptom-Checklist 90-Revised to measure psychological distress among study participants. Multivariate linear mixed effects models (LME) estimated the effect of study variables on mean change in resilience scores between 2011-2012. Results Among 191 participants, 92 % had experienced any form of childhood maltreatment, 48 % had a parent who attended residential school, and 71 % had been in foster care. The overall mean resilience score was 62.04, with no differences between the young men and women (p  = 0.871). Adjusted factors associated with higher mean resilience scores included having grown up in a family that often/always lived by traditional culture (B = 7.70, p  = 0.004) and had often/always spoken their traditional language at home (B = 10.52, p  < 0.001). Currently knowing how to speak a traditional language (B = 13.06, p  = 0.001), currently often or always living by traditional culture (B = 6.50, p  = 0.025), and having recently sought drug/alcohol treatment (B = 4.84, p  = 0.036) were also significantly associated with higher mean resilience scores. Adjusted factors associated with diminished mean resilience scores included severe childhood emotional neglect (B = −13.34, p  = 0.001), smoking crack daily (B = −5.42, p  = 0.044), having been sexual assaulted (B = −14.42, p  = 0.041), and blackout drinking (B = −6.19, p  = 0.027). Conclusions Young people in this study have faced multiple complex challenges to their strength. However, cultural foundations continue to function as buffers that protect young Indigenous people from severe health outcomes, including vulnerability to HIV and HCV infection.